LEXICAL ELEMENTS OF AIMARA IN PRESS MEDIA - Baldoceda, Ana (2012)
Spanish in Peru, practically from the first moment of the Spanish invasion, has been nourished, as it were —in vocabulary phonology and grammar— by native languages, principally Quechua and Aimara. In spite of the fact that the indigenous languages of Peru are the means of expression of a marginal sector of Peruvian society, they have never failed to enrich the dominant language in various ways, with irreplaceable words such as Aimara, Cañihuaco, Challar, Equeco, Quincha, Tunta, Yatiri, among others. In recent times, for example, the increasing presence of highland communities in social and political life has promoted the use of the word «aimara» as the name of a people when the normal use of the word was for words spoken in the throat (ethnonym, glottonym), according to what we have found in our register of magazines and newspapers.